2020
DOI: 10.1039/c9fo01718f
|View full text |Cite
|
Sign up to set email alerts
|

Oleanolic acid enhances tight junctions and ameliorates inflammation in Salmonella typhimurium-induced diarrhea in mice via the TLR4/NF-κB and MAPK pathway

Abstract: Oleanolic acid attenuates intestinal inflammation and intestinal tight junction barrier damage through the TLR4/NF-κB and MAPKs pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 42 publications
4
53
0
Order By: Relevance
“…Flow cytometry analysis showed that stimulation of A549 cells by TGF-β decreased expression of ZO-1, whereas treatment of these cells by SM effectively blocked mentioned effect: the intensity of fluorescence of the cells incubated with both TGF-β and SM was similar to that of the control untreated cells ( Figure 6B). Interestingly, that SM itself increased expression of ZO-1 in A549 cells in the absence of EMT stimulus ( Figure 6B), which agreed well with recently revealed ability of pentacyclic triterpenoids to up-regulate expression of this protein in other models [46,47].…”
Section: Sm Shifted the Expression Of Emt-associated Markers To Epithsupporting
confidence: 90%
“…Flow cytometry analysis showed that stimulation of A549 cells by TGF-β decreased expression of ZO-1, whereas treatment of these cells by SM effectively blocked mentioned effect: the intensity of fluorescence of the cells incubated with both TGF-β and SM was similar to that of the control untreated cells ( Figure 6B). Interestingly, that SM itself increased expression of ZO-1 in A549 cells in the absence of EMT stimulus ( Figure 6B), which agreed well with recently revealed ability of pentacyclic triterpenoids to up-regulate expression of this protein in other models [46,47].…”
Section: Sm Shifted the Expression Of Emt-associated Markers To Epithsupporting
confidence: 90%
“…Inflammation induced by multiple factors such as oxidative stress [2], pathogenic bacteria [31] and the increased intestinal epithelial permeability [32] has been considered as the main cause of post-weaning diarrhea. During weaning, LPS from Gram-negative bacteria can activate TLR4mediated inflammatory pathways such as nuclear factor kappa-B (NF-κB) to induce the production of inflammatory cytokines (IL-1β, IL-2, IL-6 and TNF-α) [6], which have a potential correlation with the expression of tight junction proteins [33]. In this study, both PCA and AUR significantly reduced the level of IL-6, while PCA also significantly decreased IL-2 and TNF-α level.…”
Section: Discussionmentioning
confidence: 99%
“…After normal feeding for 1 week, 6–8-weeks-old specific pathogen free female C57BL/6 mice (purchased from Changchun Yisi Experimental Animal Technology Co., Ltd., Changchun, China) were grouped into: (1) saline group ( n = 20, gavaged with 100 μL of normal saline every day for 10 days); (2) Sty group ( n = 20, gavaged with 100 μL of normal saline every day for 7 days, and given oral ST (5.19 × 10 9 cfu mL –1 day –1 p.o) on days 8–10 ( Dong et al, 2020 ); (3) treatment groups of different concentrations of CGA (60 mice were assigned into three groups with 20 mice in each group, gavaged with 10, 60, and 120 mg/kg/day of CGA (Sigma, St. Louis, MO, United States), respectively, and given oral ST (5.19 × 10 9 cfu mL –1 day –1 p.o ( n = 20) on days 8–10 after CGA treatment; (4) ST + CGA + kd-NC group ( n = 20, gavaged with 60 mg/kg/day CGA daily, given oral ST (5.19 × 10 9 cfu mL –1 day –1 p.o) on days 8–10), and injected with 100 μL of empty vector in the tail vein on days 5 and 10); (5) ST + CGA + kd-GAS5 group ( n = 20, the rest operations were the same as those in the kd-NC group, except that the tail vein was injected with 100 μL 7.8 × 10 7 IFUs GAS5 interfering vector) on the 5th day and the 10th day). Gas5 interference vector kd-GAS5, control kd-NC, and sh-NC and sh-GAS5 used in the following experiments were constructed and synthesized by Shanghai Genechem Co., Ltd. (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%